Hardy and His Readers - Wright, T. author. aut Link
X, 241 p.
Keywords: This study examines Hardy's prolonged struggle with his contemporary readers, whose bourgeois values he despised. Initially content to compromise, to provide them with congenial entertainment, Hardy resorted at first to strategies of subversion, smuggling material past his editors and finally to outspoken attack. Professor T. R. Wright attempts to balance historical research into the response of 'actual' readers and the material conditions of publishing with literary-critical analysis of the 'implied' reader inscribed in the novels themselves.